Draft Ninth Five Year Plan (1997-2002) Andhra Pradesh Volume-II (Sectoral Programmes) 5. Industries and Minerals - Government of Andhra Pradesh (Government of Andhra Pradesh, 1997)
The Draft Ninth Five-Year Plan (1997-2002) for Andhra Pradesh: Industries and Minerals Sector provides a comprehensive framework for accelerating industrial growth and optimizing the state’s mineral resources in the post-liberalization era. Guided by the New Industrial Policy “TARGET 2000,” the plan targets a 20% annual growth in the industrial sector with investments of ₹100,000 crores over five years, emphasizing the development of small, medium, and large-scale industries, alongside mineral-based enterprises. Specific initiatives include financial incentives, skill development programmes for 430,000 youth, and special support for women and SC/ST entrepreneurs, while 1,30,000 new tiny and small-scale units are projected to generate 1.3 million jobs. The plan prioritizes modernization of handlooms, expansion of sericulture, and establishment of growth centers in backward districts to foster inclusive industrial development. Significant attention is given to cooperative development, providing working capital loans, capital participation, and tax incentives to enhance rural industrial infrastructure. Investments in mineral exploration and management of 42 minerals, including limestone, coal, and precious stones, aim to strengthen industrial foundations sustainably. By integrating economic growth with social inclusivity, environmental compliance, and targeted support for marginalized groups, the Ninth Plan seeks to create a resilient industrial and mineral sector that contributes to overall socio-economic development and long-term prosperity in Andhra Pradesh.
Finance and Planning (Plg. Wing) Department Government of Andhra Pradesh October’97
Finance and Planning (Plg. Wing) Department Government of Andhra Pradesh October’97
Keywords: Andhra Pradesh; State Plan; Industrial Development; Small-Scale Industries; Mineral Resources; Sericulture; Handlooms; Skill Development; Women Entrepreneurs; Scheduled Castes; Cooperative Development; TARGET 2000